PENDEKATAN PERENCANAAN STRATEGIS DALAM PERENCANAAN TATA RUANG KOTA UNTUK PERUBAHAN IKLIM - Ruth Roselin Erniwaty Nainggolan (Institut Pemerintahan Dalam Negeri, 2024)
Greenhouse gases, which consist of 55% carbon, have been reported as the most significant contributor to climate change. Greenhouse gases have encouraged various international efforts to reduce carbon levels worldwide. One is emphasizing climate change adaptation and mitigation programs in city development. Planning is an essential element for any urban development initiative. Planning requires making choices in pursuit of stated goals. Understanding urban planning related to climate change as a